Peningkatan Hasil Belajar Siswa Dalam Pembelajaran Tematik Terpadu Tema 8 Menggunakan Model Discovery Learning Di Kelas IV SD Pembangunan Laboratorium UNP - Suci Chairul Ummah; Farida Fachrudin; Farida Suardiman (e-Journal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of this research is to improve Learning outcoes in integrated thematic learning with model Discovery Learning class VI  SD Pembangangunan Laboratorium UNP, the subject of the research is as a teacher, researcher and student of class VI, which amounted to 27 people. Results of the study showed improvements in: (a) the RPP cycle I gained an average rating of 81,815 (B) and cycle II becomes 90.90% (AB), (b) the assessment of this aspect of teacher cycle I scored average 72.91% (C) and cycle II becomes 87,5% (AB), (c) the value of the results of the study the average value of the I-cycle students 74,99% (C) and cycle II becomes 91,66% (AB).